Accreditation of nursing clinical services: Development of an appraisal tool - Sarieh Poortaghi; Mahvash Salsali; Abbas Ebadi; Nima Pourgholamamiji (Wiley, 2020)
Abstract Aim This study aimed to determine comprehensive and applicable indicators for assessing the quality of nursing clinical services. Design Methodological research. Methods The checklist was designed in three phases (conceptualization, item generation and item reduction). In the first phase, a qualitative study using conventional content analysis was performed to clarify the concept of accreditation of clinical nursing services. In the second phase, using the views of experts was obtained in phase 1 and then by a review of the literature, related items were extracted, and item pool was formed. In the last phase, validity and reliability of the checklist were examined. Result Based on three phases (Conceptualization, Item Generation and Item Reduction), the accreditation indicators of clinical nursing services were extracted in three dimensions including structure, process and outcome at two levels of organizational (including structural and outcome indicators) and individual performance appraisal (process indicators) in 19 main categories.